Taste of cherry Tam e guilass - Kiarostami, Abbas; Ershadi, Homayoun; Bagheri, Abdolhossein; Bakhtiari, Afshin; Noori, Mir Hossein; Moradi, Safar Ali.; Zeitgeist Films; CIBY 2000 (Firm); Classic Collection (Firm); Janus Films; Home Vision (Firm); Criterion Collection (Firm) ([Irvington, NY] : Criterion Collection, 1999)
Mr. Badii, ceaselessly driving through the red-brown hills around Tehran in search of assistance in his suicide, receives from each of the men he asks for help a viewpoint on life.
"The Classic Collection: a joint venture between Janus Films and Home Vision Cinema."
Originally released as a motion picture in 1997.
Special features: theatrical trailer, interview with Kiarostami by Jamsheed Akrami, filmography, scene access.
Edited by Abbas Kiarostami ; cinematography by Homayoun Payvar ; sound by Jehangir Mirshekari and Mohammad Reza Delpak ; assistant director, Hassan Yekta.
Homayoun Ershadi, Abdolhossein Bagheri, Afshin Bakhtiari, Mir Hossein Noori, Safar Ali Moradi.
DVD; Dolby digital mono.
Keywords: Kiarostami, Abbas -- Interviews; Kiarostami, Abbas; Suicide -- Drama; Assisted suicide -- Drama; Suicidio -- Drama; Assisted suicide; Manners and customs; Suicide; Iran -- Social life and customs -- Drama; Iran; Feature films; Foreign films; Drama; Feature films; Interviews